Pemakaian Partikel kah dalam Kalimat Tanya - Ary Setyadi (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2018)
AbstractParticle as a marker of the sentence type has its own characteristics/characteristics, namely: enclitis, human, and relatively free distributed. Due to the nature/ characteristics of the particle has a function as a confirmation of the sentence. In addition to the subject, the particles also have the ability to move in accordance with the elements of the sentence to be affirmed; and as a result of the ability to move in place the absence of particles can be able to join the many kinds of word classes. The application of methods, both data collection methods and methods of classification and data analysis as imposed in linguistic research activities. Namely: the stage of data collection, classification and data analysis phase, and stage of presentation/ report writing. The theory used in relation to the study of these particles is the linguistic theory of the syntactic field. The result show that the kah particle always  follow to the word. Kah particle can be remove according to the sentence elements that are focused. The existing of kah particle in the interrogative sentence is optionally. IntisariPartikel kah sebagai penanda tipe kalimat tanya mempunyai sifat/ciri khusus, yaitu:  bersifat enklitis, manasuka, dan relatif berdistribusi bebas. Akibat sifat/ciri tersebut maka partikel tersebut mempunyai fungsi sebagai penegas kalimat. Di samping perihal tersebut, partikel kah juga mempunyai kemampuan berpindah letak sesuai dengan unsur bagian kalimat yang hendak ditegaskan; dan akibat kemampuan berpindah tempat maka kebaradaan partikel kah mampu bergabung dengan sekian banyak macam kelas kata. Adapun penerapan metode, baik metode pengumpulan data maupun metode klasifikasi dan analisis data sebagaimana yang diberlakukan dalam kegiatan penelitian linguistik. Yaitu: tahap pengumpulan data, tahap klasifikasi dan analisis data, dan tahap penyajian/penulisan laporan. Teori yang digunakan sehubungan pengkajian partikel kah iniadalah teori linguistik bidang sintaksis. Hasil penelitian menunjukkan bahwa partikel kah selalu menempel pada kata. Partikel kah dapat berpindah letak sesuai dengan unsur kalimat yang dijadikan pemfokusan. Kehadiran partikel kah dalam kalimat tanya tidak bersifat wajib.